Pengaruh Kualitas Situs Web, Nilai Hedonis, Dan Nilai Utilitarian Terhadap Niat Membeli Kembali - Kusumadewi, Dyan Febrina; Soewarno, Noorlailie; Isnalita, Isnalita (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
This study aims to determine the impact of website’s quality, hedonic value, and utilitarian value toward repurchaseintention on the Lazada marketplace . Th is study consisted of 107 respondents of Lazada users collected through online surveys. The results indicate that the quality of information has a positive and significant effect on repurchase intention. While the quality of the system and service quality have no significant effect on repurchase intention . In addition, hedonic values ??and utilitarian value s have a positive and significant effect on repurchase intention. Keywords : Website quality, hedonic value, utilitarian value,  repurchase intention.